Strategi Penetapan Harga Berbasis Personal Branding Pada Platform Tiktok: Studi Netnografi - Apolonia Emriant Meo; Asti Irawati; Fadhilah Fadhilah; Nina Yusnita Yamin (ISAS, 2026)
This study aims to analyze the pricing strategies implemented by influencers in the digital era, where selling prices often exceed the intrinsic value of the product through the use of personal branding. From a management accounting perspective, this phenomenon creates a disparity between production costs (cost-based) and value-based pricing. Using a qualitative approach with netnography methods, this study explores digital consumer interactions and culture. The research data comes from netizens' comments on promotional content for the products